Using ERPs to unveil the authenticity evaluation and neural response to online rumors - Yi Ding; Xinyue Yang; Wengang Zhang; Wei Lyu; Mia Y. Wang (Scientific Reports)
Abstract The rapid propagation of information in the digital epoch has brought a surge of rumors, creating a significant societal challenge. While prior research has primarily focused on the psychological aspects of rumors—such as the beliefs, behaviors, and persistence they evoke—there has been limited exploration of how rumors are processed in the brain. In this study, we experimented to examine both behavioral responses and EEG data during rumor detection. Participants evaluated the credibility of 80 randomly presented rumors, and only 22% were able to identify false rumors more accurately than by random chance. Our ERP findings reveal that truth judgments elicit stronger negative ERP responses (N400) compared to false judgments, while false judgments are associated with larger positive ERP responses (P2, P3, and LPP). Additionally, we identified gender differences in brain activity related to rumor detection, suggesting distinct cognitive strategies. Men demonstrated greater P2 and enhanced N400 responses, while women exhibited larger P3 and LPP amplitudes. This study is among the first to investigate the neural patterns underlying rumors recognition and to highlight gender disparities in decision-making related to rumors.